Clinical diagnosis and therapy of opsoclonus-myoclonus syndrome - Xiong, Hui (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2008)
OBJECTIVE: Clinical manifestations of opsoclonus-myoclonus syndrome (OMS) in children were summarized and analyzed and the clinical features and therapeutic approaches to OMS were investigated in order to improve its diagnosis and management